The Impact of Intensified Aridization Caused by Moisture Deficit on the Productivity of Grain Crops in Northern Kazakhstan - Kusainova, Aisulu Amirkhanovna; Chistyakova, Galina Nikolaevna; Zhangozhina, Gaukhar Makhanovna (Research in Ecology, 2025)
The article examines the impact of increased aridization of the territory due to an increase in air temperature, reduced precipitation, and the formation of moisture deficiency on grain yields in Northern Kazakhstan. The most important result of the work is the revealed inverse relationship between grain yields and the temperature of the growing season: low-yielding years are associated with high temperatures and droughts, and high-yielding years are associated with lower temperatures and an optimal ratio of heat and moisture. The novelty of this study is the use of the method of hydrological and climatic calculations in identifying the nature of temperature variability and precipitation in the territory of Northern Kazakhstan for the modern period (1991–2020) compared with the base period (1961–1990). At all the studied meteorological stations, there is a tendency for the average annual temperature and the temperature of the growing season to increase: in the forest-steppe zone with an average warming intensity of 0.3–0.33 °C per decade; in the steppe zone by 0.2–0.43 °C per decade; and in the growing season by 0.2–0.7 °C per decade. The air temperature in the steppe zone is rising more intensively than in the forest-steppe zone, and precipitation in the forest-steppe zone has changed more than in the steppe zone. An increase in the average annual air temperature during the growing season (May–August), combined with a shortage of atmospheric moisture or a constant amount of it, led to an increase in the degree of aridization of the territory, an increase in the frequency of droughts in the steppe zone of Northern Kazakhstan.